Descriptions of larvae of four species of Hydropsyche (Hydropsychidae: Trichoptera) from Thailand - Prommi, Taeng On (Zootaxa, 2016)
Morphological characters of the larvae of four species in the genus Hydropsyche (H. dolosa, H. brontes, H. napaea, and H. camillus) are described and figured for the first time. The most important diagnostic features are illustrated, and some information regarding their distribution, biology, and habitat are included.